Pengaruh pendidikan kesehatan tentang bantuan hidup dasar (BHD) terhadap tingkat pengetahuan anggota PMR di SMK N 1 Bawen: The Influence Of Health Education On Basic Life Support (BLS) On The Level Of Knowledge Of PMR Members at SMK N 1 Bawen - Susilo, Tri; Maksum; Mustain, Mukhamad (Chakra Brahmanda Lentera Institute, 2022)
BHD emergency measures are carried out to free the airway, assist breathing and maintain blood circulation without the use of assistive devices. Emergency can occur anytime, anywhere, and to anyone. Victims need a form of help that is fast and appropriate so that the victim can avoid the danger of death. First aid knowledge in accidents should be owned by PMR members. One of the efforts to provide information is through counseling or health education, which is expected to increase the knowledge of PMR members. This study aims to determine the effect of health education on basic living rock (BHD) on the level of knowledge of PMR members at SMK N 1 Bawen. The design of this study used a pre-experimental design with a one group pre-test-post-test design approach. The population in this study were 35 members of PMR at SMK N 1 Bawen. The sampling technique in this research is purposive sampling. Data analysis used univariate and bivariate analysis using Wilcoxon test. Health knowledge about basic living rock (BHD) in PMR members before health education has an average value of 71.22, after health education has an average value of 87.78. There is an effect of health education on basic living rock (BHD) on the level of knowledge of PMR members obtained a p-value of 0.0001> 0.05. There is an effect of health education on basic living rock (BHD) on the level of knowledge of PMR members. The results of this study provide input to SMK N 1 Bawen so that they can conduct training on the handling of basic living rock (BHD) for PMR members.